Bovine Anaplasmosis: Will there ever be an almighty effective vaccine? - Salinas-Estrella, Elizabeth; Amaro-Estrada, Itzel; Cobaxin-Cárdenas, Mayra E.; Preciado de la Torre, Jesús F.; Rodríguez, Sergio D. (Frontiers in Veterinary Science, 2022)
Bovine anaplasmosis is a tick-borne bacterial disease with a worldwide distribution and the cause of severe economic losses in the livestock industry in many countries, including México. In the present work, we first review the elements of the immune response of the bovine, which allows ameliorating the clinical signs while eliminating the majority of the blood forms and generating an immunologic memory such that future confrontations with the pathogen will not end in disease. On the other hand, many vaccine candidates have been evaluated for the control of bovine anaplasmosis yet without no commercial worldwide effective vaccine. Lastly, the diversity of the pathogen and how this diversity has impaired the many efforts to control the disease are reviewed.